PENGARUH PENERAPAN AKUNTANSI SEKTOR PUBLIK DAN TRANSPARASI LAPORAN KEUANGAN TERHADAP KINERJA PELAYANAN DI GEREJA KRISTEN INDONESIA (GKI) NURDIN - Aulia, Reva (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to examine how the application of public sector accounting and the level of transparency in financial reporting affect service performance at the Indonesian Christian Church (GKI) Nurdin. As a non-profit organization, the church requires responsible and transparent financial management to support the effectiveness of its services. This study uses a quantitative method, with primary data obtained through the distribution of questionnaires to 25 young members of the congregation at GKI Nurdin. Data processing in this study was carried out using multiple linear regression analysis techniques. The findings of this study indicate that the application of public sector accounting has a positive and significant impact on improving service performance. Conversely, financial report transparency does not have a significant impact.